Evaluation of acute and sub-chronic toxicities of ulcer fast®: a bi-herbal formula in male Wistar albino rats - Patrick-Iwuanyanwu, Kingsley C.; Emerue, Jane A. (International Journal of Basic & Clinical Pharmacology, 2017)
The acute and sub-chronic toxicities of ulcer fast® (UF) - A commercial bi-herbal formula prepared with Alstonia boonei and Xylopia aethiopica in male Wistar albino rats was evaluated. There was no mortality in rats administered 2000 mg/kg body weight (BW) of UF in an acute toxicity study. A significant (p≤0.05) increase in daily consumption of feed and fluid intake in experimental rats after 28 days was recorded followed by a progressive increase in BW of rats administered 50, 100 and 200 mg/kg BW of UF in a dose-dependent manner. Alanine amino transferase, aspartate amino transferase, alkaline phosphatase, lactate dehydrogenase, triacylglycerides and creatinine increased significantly (p≤0.05) in rats treated with UF, whereas urea and fasting blood sugar decreased significantly (p≤0.05) in a dose-dependent manner when compared with control. There was a marginal decrease in serum calcium ion and phosphate ion following the administration of UF when compared with control. Packed cell volume and hemoglobin decreased significantly (p≤0.05) in rats treated with UF, whereas white blood cell increased significantly (p≤0.05) in a dose-dependent manner when compared with control. Histological examination of the liver, kidney, heart and lungs showed normal architecture in control group, whereas hepatocytes of rats treated with 50, 100 and 200 mg/kg BW of UF were characterized by slight periportal fatty change, marked change and ballooning degeneration. Heart muscle of rats treated with 200mg/kg BW of UF showed slight inflammation while histological examination of the lungs showed areas of interstitium damage and diffuse alveolar damage in rats treated with UF. In conclusion, indiscriminate administration of UF could be of public health concern and long-term exposure may cause a significant potential health risk.